Thick-walled composite tubes for offshore applications: an example of stress and failure analysis for filament-wound multi-layered pipes. (3rd April 2017) - Guz, Igor A.; Menshykova, Marina; Paik, Jeom Kee
Abstract : The paper reviews practical applications of composite materials in oil and gas industry. A special consideration has been paid to possible future opportunities in offshore and onshore usage; in particular, to long fibre-reinforced composite pipes. The problem of thick-walled filament-wound multi-layered composite pipes subjected to outer pressure is considered as an example. An analytical method is used for failure analysis for different lay-ups and loading conditions. The stress distributions through the pipe thickness for various lay-ups are computed for fibre-reinforced pipes under different outer pressure magnitudes.